Organic Carbon and Nitrogen Stocks Along a Thermokarst Lake Sequence in Arctic Alaska. Issue 5 (15th May 2019) - Fuchs, Matthias; Lenz, Josefine; Jock, Suzanne; Nitze, Ingmar; Jones, Benjamin M.; Strauss, Jens; Günther, Frank; Grosse, Guido
Abstract: Thermokarst lake landscapes are permafrost regions, which are prone to rapid (on seasonal to decadal time scales) changes, affecting carbon and nitrogen cycles. However, there is a high degree of uncertainty related to the balance between carbon and nitrogen cycling and storage. We collected 12 permafrost soil cores from six drained thermokarst lake basins (DTLBs) along a chronosequence north of Teshekpuk Lake in northern Alaska and analyzed them for carbon and nitrogen contents. For comparison, we included three lacustrine cores from an adjacent thermokarst lake and one soil core from a non thermokarst affected remnant upland. This allowed to calculate the carbon and nitrogen stocks of the three primary landscape units (DTLB, lake, and upland), to reconstruct the landscape history, and to analyze the effect of thermokarst lake formation and drainage on carbon and nitrogen stocks. We show that carbon and nitrogen contents and the carbon‐nitrogen ratio are considerably lower in sediments of extant lakes than in the DTLB or upland cores indicating degradation of carbon during thermokarst lake formation. However, we found similar amounts of total carbon and nitrogen stocks due to the higher density of lacustrine sediments caused by the lack of ground ice compared to DTLB sediments. In addition, the radiocarbon‐based landscape chronology for the past 7, 000 years reveals five successive lake stages of partially, spatially overlapping DTLBs in the study region, reflecting the dynamic nature of ice‐rich permafrost deposits. With this study, we highlight the importance to include these dynamic landscapes in future permafrost carbon feedback models. Plain Language Summary: When permanently frozen soils (permafrost) contain ice‐rich sediments, the thawing of this permafrost causes the surface to sink, which may result in lake formation. This process, the thaw of ice‐rich permafrost and melting of ground ice leads to characteristic landforms—known as thermokarst . Once such a thaw process is initiated in ice‐rich sediments, a thaw lake forms and grows by shoreline erosion, eventually expanding until a drainage pathway is encountered and the lake eventually drains, resulting in a drained thermokarst lake basin. In our study, we show that such a thermokarst‐affected landscape north of Teshekpuk Lake in northern Alaska is shaped by repeated thaw lake formation and lake drainage events during the past 7, 000 years, highlighting the dynamic nature of these landscapes. These landscape‐scale processes have a big effect on the carbon and nitrogen stored in permafrost soils. We show that large amounts of carbon (>45 kg C/m 2 ) and nitrogen (>2.6 kg N/m 2 ) are stored in unfrozen lake sediments and in frozen soil sediments. The findings are important when considering the potential effect that permafrost thaw has for the global climate through releasing carbon and nitrogen, which was frozen and therefore locked away for millennia, from the active carbon cycle. Key Points: This study combines terrestrial and lacustrine cores for carbon and nitrogen stock estimates in an ice‐rich permafrost region Even though organic matter is degraded in thawed lake sediments, similar C and N stocks are found in terrestrial and lacustrine sediments Up to five thermokarst lake stages shaped the study area in the last 7, 000 years indicating the high dynamics of thermokarst lake landscapes